PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KINERJA GURU TERHADAP MUTU PENDIDIKAN PADA SMP SWASTA BINAAN DI KUPANG - Isak Ano Marthen Kolihar; Hendrik A.E Lao; Yakobus Adi Saingo (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This research aims to find out to what extent the influence of the leadership of the head of the school and the performance of teachers on the quality of education in the first private secondary school of the district of Kupang. The method used in this survey is a survey method with a quantitative approach. Data collection techniques are used through questionnaires / survey, observations and documentation / documentary to understand the influence of the head of school leadership and teacher performance on the quality of education. The results of the research obtained by the researchers from the results of a summary model test are: 1) The value of the influence of the variable Leadership of the head of school (X1) on the quality variable of education (Y) received the value of R square or R2 = 0,770 = 77,0%. The values show that the leadership variable of the head of school (X1) has an impact on the quality of education (Y) of 77,0%, which means that the leader of the school has a very significant contribution to the improvement of education quality. 2) The value of the influence variable Teacher Performance (X2) on the variable quality of education (Y) is obtained Value R square or R2 = 0.715 = 71.5%. The value shows that the teacher performance variable (X2) has an influence on the quality of education (Y) of 71.5%, meaning that the performance of teachers has a very significant contribution to the improvement of the education quality. The impact of the variables Leadership of the head of school (X1) and Teacher Performance (X2) on the variable quality of education (Y) obtained the value of R square or R2 = 0,830 = 83,0%. The value showed that the variation of the variable of the head of school leadership (X1) and the teacher performance variable (X2) on the quality of education (Y) had an impact of 83,0%, meaning that simultaneously the leadership of the school head and the performance of teachers have a very significant contribution to the improvement of the quality in education. Thus it can be concluded that the leadership of the head of school and the performance of teachers have a significant influence on the quality of education